Analisis Tata Kelola Aplikasi BMKGSOFT Dengan Menggunakan Framework COBIT 2019 Studi Kasus Badan Meteorologi Klimatologi Dan Geofisika Provinsi Lampung - Rizki Cahyadi Okasumaendy; Wasilah (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
In Law Number 31 of 2009, MKG information has a strategic role in improving the safety of life and property, the economy, as well as defense, and security. Therefore, the management of MKG data is important so that the implementation of MKG is not hampered. Following up on this, BMKG implemented E-Government by developing an integrated, centralized, online data management system and facilitating data access called the BMKGSoft System. In its implementation, various problems indicate an irregularity in the implementation of the BMKGSoft system. This study aims to audit the governance of the BMKGsoft database application using the COBIT 2019 framework with the MEA01, MEA02, and MEA03 domains to see how far the performance of the BMKGsoft application has been achieved. Performing a GAP analysis on the performance of the BMKGsoft database application system and designing recommendations for improvement so that the application can be utilized. The results of this study MEA01, MEAO2, and MEA03 obtained level 4 (Predictable Process) in capability and maturity level. It can be said to have implemented IT processes to achieve its objectives, it is well defined, and its performance (quantitatively) can be measured against the defined attributes. Furthermore, suggestions and improvements are given to combining several frameworks in conducting further research for comparison.